2022
DOI: 10.3389/fenrg.2022.774760
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Algae Biofilm Reactor for Management and Valorization of Produced Wastewater

Abstract: Production and enhancement of high value phycocyanin pigment from microalgae biofilms cultured on oilfield and natural gas produced wastewater were investigated. Cyanobacteria isolated from Logan City, Utah, wastewater treatment Lagoons (LLC2) was cultured in produced water using rotating algal biofilm reactors (RABRs). The RABRs were operated under “low” and “high” light conditions and biomass and phycocyanin content were compared. Phycocyanin content was enhanced by growth under low light conditions to a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Currently, the design of algal biofilm bioreactors is mostly focused on different geometrical configurations and different support or attachment materials. Some examples of contemporary biofilm systems in microalgae cultivation for diverse purposes include flat rotating disks (Blanken et al 2014 ), cylindrical rotating drums (Christenson and Sims 2012 ), and conveyor rotating belts (Gross et al, 2013 ; Wood et al 2022 ). As compared to conventional harvesting methods including membrane filtration, centrifugation, and sedimentation, algal biofilm harvesting can overcome the high cost and energy consumption associated with it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the design of algal biofilm bioreactors is mostly focused on different geometrical configurations and different support or attachment materials. Some examples of contemporary biofilm systems in microalgae cultivation for diverse purposes include flat rotating disks (Blanken et al 2014 ), cylindrical rotating drums (Christenson and Sims 2012 ), and conveyor rotating belts (Gross et al, 2013 ; Wood et al 2022 ). As compared to conventional harvesting methods including membrane filtration, centrifugation, and sedimentation, algal biofilm harvesting can overcome the high cost and energy consumption associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of various materials, such as natural and synthetic substrates, in the creation of algal biofilms, has been the subject of much research (Christenson and Sims 2012 ; Genin et al 2014 ; Venable and Podbielski 2019 ). It has been demonstrated that cotton (Wood et al 2022 ; Christenson and Sims 2012 ; Gross and Wen 2014b ), nylon mesh (Lee et al 2014 ), and polystyrene foam (Johnson and Wen 2010 ) have been proven best performers in terms of cell binding, durability and cost of the support material.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating algae biofilm reactors (RABRs) have been used to combine nutrient recovery from wastewater through uptake by attached‐growth microalgal biofilms with harvesting by physical scraping from a growth surface. RABR biofilms cultivated on municipal and industrial wastewaters have been demonstrated to serve as feedstocks for microbial and chemical transformations to value bioproducts that include biofuels, biofertilizers, bioplastics, and chemicals for improved animal gut health and plant growth (Chew et al, 2017; Wood et al, 2022). Engineering challenges related to algae‐based biofilm reactors for these dual applications have been reviewed and addressed (Arora et al, 2021; Christenson & Sims, 2012; Kesaano & Sims, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike common tertiary treatments (e.g., flocculation, tertiary filters, or chlorine disinfection), algae sequester nitrates and phosphates from wastewater without producing carcinogenic byproducts [11,12]. The rotating algal biofilm (RAB) reactor system is exclusively developed to grow algae and can be used in multiple areas [13]. RAB-integrated WRRFs can be utilized to treat wastewater in the form of secondary or tertiary treatments via nutrient removal, industrial pretreatment, and side stream treatment such as anaerobic digestion effluents, as well as producing algal biomass, as shown in Figure 1B.…”
Section: Introductionmentioning
confidence: 99%